Preparation and Characterization of Organic-Inorganic Hybrid Coating Surface with Gradient Wettability - Zhou, Liang; Huang, Ziheng; Tao, Yuhong; Cheng, Jiang (Asian Journal of Chemistry, 2015)
The organic-inorganic hybrid coating surface with gradient wettability of water contact angle from 12.0 to 85.3° was prepared by slowly adding hexamethoxy methyl melamine and subsequently fluoro-contained acrylic polymer into an organic-inorganic hybrid hydrophilic polymer synthesized by tetraethoxysilane (TEOS) and acrylic acid (AA) while the microslide substrate was gradually lifted up from the above mixture. After finally taken out from the solution the coated microslide was then cured in an oven at 220 °C for 90s to form the wettability gradient surface. X-ray photoelectron spectroscopy was employed to characterize the surface chemical composition of the gradient surface. The method overcomes the limitation of restrictive substrate and reactive conditions, providing potential applications in areas such as protein absorption, microfluidics and heat transfer enhancement.